ABIOTIC FORMATION OF HYDROCARBONS UNDER HYDROTHERMAL CONDITIONS: CONSTRAINTS FROM CHEMICAL AND ISOTOPE DATA - Fu Q.; Seyfried W.E.; Sherwood Lollar B.; Lacrampe-Couloume G.; Horita J. (My University, 2007)
To understand reaction pathways and isotope systematics during mineral-catalyzed abiotic synthesis of hydrocarbons under hydrothermal conditions, experiments involving magnetite and CO2 and H2-bearing aqueous fluids were conducted at 400 °C and 500 bars. A robust technique for sample storage and transfer from experimental apparatus to stable isotope mass spectrometer provides a methodology for integration of both carbon and hydrogen isotope characterization of reactants and products generated during abiogenic synthesis experiments. Experiments were performed with and without pretreatment of magnetite to remove background carbon associated with the mineral catalyst. Prior to experiments, the abundance and carbon isotope composition of all carbon-bearing components were determined. Time-series samples of the fluid from all experiments indicated significant concentrations of dissolved CO and C1-C3 hydrocarbons and relatively large changes in dissolved CO2 and H2 concentrations, consistent with formation of additional hydrocarbon components beyond C3. The existence of relatively high dissolved alkanes in the experiment involving non-pretreated magnetite in particular, suggests a complex catalytic process, likely involving reinforcing effects of mineral-derived carbon with newly synthesized hydrocarbons at the magnetite surface. Similar reactions may be important mechanisms for carbon reduction in chemically complex natural hydrothermal systems. In spite of evidence supporting abiotic hydrocarbon formation in all experiments, an "isotopic reversal" trend was not observed for 13C values of dissolved alkanes with increasing carbon number. This may relate to the specific mechanism of carbon reduction and hydrocarbon chain growth under hydrothermal conditions at elevated temperatures and pressures. Over time, significant 13C depletion in CH4 suggests either depolymerization reactions occurring in addition to synthesis, or reactions between the C1-C3 hydrocarbons and carbon species absorbed on mineral surfaces and in solution. © 2007 Elsevier Ltd. All rights reserved.